Tradeoff study of heat sink and output filter volume in a GaN HEMT based single-phase inverter - Gurpinar, Emre; Castellazzi, Alberto (IEEE, 2017)
This paper presents the trade-off study of heat sink and output filter volume of a GaN HEMT based single phase inverter. The selected topology is three-level Active Neutral point Clamped (ANPC) inverter, and the main aim is to explore the benefits of the GaN HEMTs at 600 V blocking class on the system level efficiency, and power density under wide range of operating conditions. The paper starts by introducing the inverter topology, selected PWM scheme and followed by the device features, static and dynamic characterisation and continues with presenting and discussing the results of extensive experimental and analytical characterisation. After this, the impact of GaN HEMTs on inverter volume is discussed in terms of heat sink and output filter volume analysis under different switching frequency and heat sink temperature conditions. The calculation of heat sink volume and single stage LC output filter volume are presented with respect to experimental results of single phase prototype. The findings from static, dynamic characterisation and single phase prototype results clearly show that GaN HEMT has excellent switching performance under wide load current and heat sink temperature conditions. The high performance of the inverter lead to reduction of the combined total volume, including output filter and heat sink volume.